Pelatihan Pengolahan Limbah Kulit Pisang Menjadi Minuman Susu Di Daerah Transmigrasi Lokal Kabupaten Bantul - Kusmartono, Bambang; Yuniwati, Murni; wahyu Sheilma (DHARMA BAKTI, 2024)
Karangtengah Area, Imogiri District, Bantul Regency, Special Region of Yogyakarta, is a Transmigration Location that is fostered by the Bantul Regency Manpower and Transmigration Office. This area is a center for the production of fried culinary foods such as fried tempeh, fried tofu, fried bananas and so on which are quite well-known by the wider community. Coaching is carried out by providing training to improve the insight and skills of residents in solving problems and utilizing the potential that exists in the location. Culinary products that can be enjoyed by the community include fried bananas, but this activity also produces waste in the form of unused banana peels. Utilizing banana peel waste into useful products with appropriate technology is the goal of coaching activities for the Karangtengah community carried out by the Chemical Engineering Study Program, AKPRIND University. The product that will be produced from processing banana peel waste is a milk drink, a product that has high nutritional value at an affordable price.The activity method is carried out by presenting on material related to banana peel and its utilization to residents, discussions, questions and answers about the material presented, followed by training in skills to make milk drinks from banana peel and green beans, and mentoring for residents who want to practice it themselves. With the right technology, banana peel waste can be processed into nutritious and inexpensive drinks, so that it can help government programs in improving community nutrition, especially lower-middle class people.